Amor e Guerra: a representação fotográfica do espaço bélico nas imagens de Lynsey Addario - Santos, Ellen Cristina Moreira (2022)
The presence, participation and recognition of women in the war camp have grown, because of their trajectories and productions are, still, little discussed as to their importance in the documentation of the history of war photographs. The general objective of this dissertation is to analyze war photographs taken by women photojournalists within the war space, in order to understand how gender questions manifest themselves in this space. It is justified by reason of how war is considered a masculine environment, with photography being able to reinforce this convention, many times photographers are made invisible or their productions are little analyzed. The specific objectives consist of: recounting the history of war photography, from a gender perspective; parents understand that the feminine gender is possui in traditionally masculinized spaces; to present photographers who are inserted in the war space; to explain what characterizes the war space and its relationship with everyday life and to investigate its photographic productions. The theoretical foundation has studies on gender (BUONANNO) and photography (SONTAG), applied to war, with concepts on the war space (BUTLER; HIIK) and everyday life (BECK). The corpus of the research part of the documentary and photographic analysis of the images of the photojournalist Lynsey Addario, present in the photobook Of Love & War (2018). Through research, it was possible to understand how the photographer's war photographs are produced and what they reveal about the war space and everyday life in war.